New technology for stroke rehabilitation - Moshonkina, Tatiana; Zharova, Elena; Ananydev, Sergey; Shandybina, Natalia; Vershinina, Elena; Lyakhovetskii, Vsevolod; Grisin, Aleksandr; Gerasimenko, Yuri (Nepal Journal of Neuroscience, 2025)
A study was conducted using the "Spinal neuroprosthesis neurostimulation device" specs 26.60.13-004-65248030-2021, which is designed to stimulate the dorsal roots of the cervical and lumbar spinal branches by rhythmic electrical stimulation during defined phases of the step cycle.The aim of the study was to evaluate the safety and efficacy of a neuroprosthesis to regulate motor functions in patients with the consequences of an acute cerebrovascular accident.Group 1 (main group): Patients who underwent transcutaneous electrical spinal cord stimulation with a neuroprosthesis and standard rehabilitation (therapeutic exercises, massage, physiotherapy). Group 2 (control): Patients who underwent electrical stimulation with a neuroprosthesis without current and standard rehabilitation. Primary efficacy point: improvement in walking performance in the 10-metre walk test and the 6-minute walk test.Secondary efficacy points: Improvement in performance tests on various scales: Fugl-Meyer, the Medical Research Council Scale for Muscle Strength , quantitative muscle strength assessment, Berg Balance Scale, Functional Independence Scale, modified Ashworth Scale and analysis of spatio-temporal and kinematic parameters assessed by laboratory methods, video recording of muscle activity. The rehabilitation course consisted of 12 daily procedures, each lasting 40-60 minutes and performed on a treadmill for 20 minutes. Tests were performed 1-2 days before the start of the rehabilitation course and the day after the rehabilitation course ended.The results of a clinical study showed that the use of a neuroprosthesis leads to a significant improvement in muscle strength, the ability to maintain balance, a decrease in spasticity and an increase in functional independence.